1986
DOI: 10.1136/jcp.39.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic haemochromatosis and HLA antigens in Italy: is A3 Bw35 HLA haplotype a marker for idiopathic haemochromatosis gene in north east regions?

Abstract: SUMMARY Thirty two unrelated Italian subjects with idiopathic haemochromatosis were studied. HLA-A3 was present in 26 of them (81% v 22% in controls; p < 0 001) and HLA B7 in eight (28% v 9%; p < 0-01). There was no important association between idiopathic haemochromatosis and HLA B14. Subdividing the patients on the basis of their regional origin a noticeably higher prevalence ofHLA Bw35 in patients with idiopathic haemochromatosis from north eastern Italy was found than in those from Lombardy, or in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
2
12
1
Order By: Relevance
“…Zacchi et al [3] recently reported the association of IH with A3,B35 in patients from Friuli. This finding was further suggested by Piperno et al [4] in patients from Veneto and Friuli. This unique association is con firmed by our study: the prevalence of A3,B35 was significantly higher in patients than in controls, and all haemochromatotic subjects carrying B35 also had A3.…”
Section: Hla Haplotypessupporting
confidence: 68%
See 4 more Smart Citations
“…Zacchi et al [3] recently reported the association of IH with A3,B35 in patients from Friuli. This finding was further suggested by Piperno et al [4] in patients from Veneto and Friuli. This unique association is con firmed by our study: the prevalence of A3,B35 was significantly higher in patients than in controls, and all haemochromatotic subjects carrying B35 also had A3.…”
Section: Hla Haplotypessupporting
confidence: 68%
“…It is worthwhile to note a lesser prevalence of B35 in our patients (0.44) compared to that reported by Piperno et al [4] in patients from both Veneto and Fri uli (0.75). The absence of cases from Friuli in our study might explain such a difference.…”
Section: Hla Antigenscontrasting
confidence: 51%
See 3 more Smart Citations